Semiconductor Jujitsu. (Wilson Quarterly)
Presents a review of an article about the United States semiconductor industry entitled `Reversal of Fortune? The Recovery of the U.S. Semiconductor Industry,' by Jeffrey T. Macher which appeared in the Fall 1998 issue of `California Management Review.'